2014
DOI: 10.1530/joe-14-0333
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory roles of the mammalian GnIH ortholog RFRP3 in testicular activities in adult mice

Abstract: The aim of this study was to evaluate the effects of in vivo and in vitro treatments with RFamide-related peptide 3 (RFRP3), a mammalian gonadotropin-inhibitory hormone ortholog, on testicular activities, i.e. spermatogenesis and steroidogenesis, in mice. Mice were treated in vivo with different doses of RFRP3 (control: 0.02 mg, 0.2 mg, and 2.0 mg/day) for 8 days. For in vitro study, the testes of mice were evaluated with different doses of RFRP3 (control: 1 and 10 ng/ml) with or without LH (control: 10 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Thus, testicular stimulation/inhibition of sex steroid production and testicular cell survival/apoptosis appears to be the outcome of local (through testicular GnIH and its receptor) effects, which may be also altered by the temporal phase relation of neural oscillations. It is well documented from both in vitro and in vivo analyses that the mammalian GnIH ortholog RFRP3 has a direct effect on testicular steroidogenesis in mice (Anjum et al, 2014). The GnRH-GnIH system, through their receptors, may play a role in the autocrine/paracrine regulation of testosterone production and regulate optimal testicular activity in birds and mammals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, testicular stimulation/inhibition of sex steroid production and testicular cell survival/apoptosis appears to be the outcome of local (through testicular GnIH and its receptor) effects, which may be also altered by the temporal phase relation of neural oscillations. It is well documented from both in vitro and in vivo analyses that the mammalian GnIH ortholog RFRP3 has a direct effect on testicular steroidogenesis in mice (Anjum et al, 2014). The GnRH-GnIH system, through their receptors, may play a role in the autocrine/paracrine regulation of testosterone production and regulate optimal testicular activity in birds and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (2011) has demonstrated the direct inhibitory effect of GnIH on ovarian steroidogenesis in mice. Anjum et al (2014) showed the direct effect of RFRP3 in vitro and in vivo on testicular steroidogenesis in mice, and different doses of RFRP3 resulted in a significant decrease in testosterone synthesis in mice testes. GnIH modulates testosterone production and spermatogenesis directly as well as indirectly through its paracrine and endocrine function, mediated via its receptors present in the Sertoli, Leydig and germ cells .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment of prehierarchial follicular granulosa cells with GnIH significantly decreased basal but not FSH-stimulated cellular viability in vitro (Maddineni et al, 2008b). Anjum et al (2014) evaluated the effects of RFRP-3 on testicular activities, spermatogenesis and steroidogenesis, in vivo and in vitro in mice. RFRP-3 treatment caused dose-dependent histological changes in spermatogenesis, such as decline in germ cell proliferation and survival markers and increase in apoptotic markers.…”
Section: Pg 22mentioning
confidence: 99%
“…In addition to central action of GnIH, direct regulation of gonadal activity by GnIH is becoming clear. GnIH and GnIH receptor are expressed in steroidogenic cells and germ cells in gonads in birds and mammals (Anjum et al, 2014;Bentley et al, 2008;Oishi et al, 2012;Singh et al, 2008Singh et al, , 2011aSingh et al, , 2011bZhao et al, 2010), and GnIH possibly acts by an autocrine/paracrine manner to suppress gonadal steroid production and germ cell differentiation and maturation (Anjum et al, 2014;Bentley et al, 2008;Oishi et al, 2012;Singh et al, 2008Singh et al, , 2011aSingh et al, , 2011bZhao et al, 2010).…”
Section: Direct Regulation Of Gonadal Activity By Gnihmentioning
confidence: 99%